2010
DOI: 10.1194/jlr.m000729
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of desnutrin functional domains: critical residues for triacylglycerol hydrolysis in cultured cells

Abstract: Triacylglycerol (TAG) serves as the major energy reserve in higher eukaryotic organisms ( 1 ). FFAs are mobilized from TAG through the hydrolytic action of lipases to provide substrates for oxidative metabolism in tissues, as well as substrates for synthesis of complex lipids and signaling molecules. Lipolysis, the breakdown of TAG to FFA and glycerol, occurs in an orderly and regulated manner, with different enzymes acting sequentially at each step ( 1-3 ). Hydrolysis of TAG to diacylglycerol is the fi rst st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
61
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 27 publications
4
61
3
Order By: Relevance
“…4) and altering either Ser 47 or Asp 166 abolishes triglyceride lipase activity (44,45). Furthermore, in the present study, the C-terminal truncated variants of PEDF-R demonstrated PLA 2 activity similar to that of full-length PEDF-R.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…4) and altering either Ser 47 or Asp 166 abolishes triglyceride lipase activity (44,45). Furthermore, in the present study, the C-terminal truncated variants of PEDF-R demonstrated PLA 2 activity similar to that of full-length PEDF-R.…”
mentioning
confidence: 48%
“…we used nanolipoprotein particles to improve the folding of recombinant polypeptides) could explain this discrepancy. Other reports describe the presence of an inhibitory region toward the C-terminal end of PEDF-R (44,47,48). This region does not seem to be inhibitory for PLA 2 activity because the C-terminal truncated variants of this study exhibit PLA 2 activity identical to that of full-length polypeptides.…”
mentioning
confidence: 71%
“…ATGL activity does not appear to be regulated directly by PKA phosphorylation, although preliminary evidence in mammalian cells indicates that ATGL is phosphorylated by other unknown kinases (84). A phosphoprotein proteomic analysis of purified LDs reported phosphorylation at Ser 404 and Ser 428 of human ATGL (4); however, site-directed mutagenesis of these sites did not affect TG breakdown under basal conditions (20). Hence, the reason for ATGL phosphorylation in cells is currently unresolved, as are the upstream kinases.…”
Section: Regulation Of Tg Lipasesmentioning
confidence: 99%
“…Biochemical evaluation of cell lysates and high-resolution imaging of fluorescence reporters in living cells also show that ATGL resides in the cytoplasm and on lipid droplets (LD) in the basal state (28,84), and cAMP-dependent protein kinase (PKA) activation elicits only minor translocation of ATGL to LDs (28). The COOH-terminal region of ATGL that contains a hydrophobic region is essential for this appropriate cellular localization and association with LDs (45,65), whereas the NH 2 -terminal region (residues 10 -24) appears to be important for TG binding (20). ATGL activity does not appear to be regulated directly by PKA phosphorylation, although preliminary evidence in mammalian cells indicates that ATGL is phosphorylated by other unknown kinases (84).…”
Section: Regulation Of Tg Lipasesmentioning
confidence: 99%
See 1 more Smart Citation